(untitled) (Research, Society and Development, 2023)
Breast cancer, like most cancers, fits into a group of diseases that have multifactorial causes, that is, multiple etiological factors, whether genetic or environmental. The way in which the factors interact and cause the disease is still not fully understood. Screening in asymptomatic populations seeks to change the prognosis. Screening exams in general include mammography, clinical breast exam, among others. Within the scope of the Covid-19 pandemic and the situation of social isolation, the present study aimed to evaluate the incidence of breast cancer and the respective therapies in the pre-pandemic and pandemic period in the city of Cascavel-PR, based on data provided by the government in Data SUS. The results indicated that during the pandemic, deaths in the city remained stable, in contrast to the numbers indicated in the national scope. There was an increase of 72% in diagnoses in the period and 15% in treatments, in contrast to the reduction in mammography exams, in a proportion of 58% in the year 2020; and in 2022, the rate of surgeries increased by more than 150% compared to 2021. It can be concluded that there was an increase in diagnoses and prevalence, after the year 2021, due to surgical intervention. However, it is not possible to relate the increase in diagnoses to the Covid-19 virus, but to public policies of social isolation, reduction of mammograms, possible selectivity and assertive advances in diagnoses.